Pemberdayaan Masyarakat di Kelurahan Klamalu Kabupaten Sorong (Pelatihan Pemanfaatan Ubi Keladi dan Pelabelan Produk) - -, Susetyowati Sofia; Muhammad Amin; Digor Mufti; Roland Kukurlue; Lince Levina waromi; Priska Gloria bowaire; Meis Mawo Kombado; Salimah Salimah; Nurul Anjani; Kartika Shandy Natalia Kirioma (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Ideas and plans in building a business venture must be well designed. Business planning is used as a guide for business people in running a business. Seeing the large potential of taro tubers which are usually processed only as daily food preparations without processing them into products that can be sold with a higher selling value. Therefore, there is a new innovative idea for managing taro taro into a taro chips business idea. This community service training method is carried out through several stages as follows: observation, licensing, preparation, implementation, discussion and question and answer, material reinforcement. The activities can be concluded that the people of Klamalu sub-district are enthusiastic in attending community empowerment activities, the audience is enthusiastic in watching the presentation of material about the use of taro, the audience also participates in the practical process of processing taro chips, the audience can also add new insights about labeling which can be developed to increase additional income for housewives.